2005
DOI: 10.1111/j.0022-202x.2004.23608.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Tracking Phospholipid Permeation into Skin Using Infrared and Raman Microscopic Imaging

Abstract: The feasibility of monitoring the permeation of chain perdeuterated 1,2-dipalmitoylphosphatidylcholine (DPPC-d62) and 1-palmitoyl-d31, 2-oleoylphosphatidylcholine (P-d31OPC) vesicles into pigskin using infrared (IR) microscopic imaging and confocal Raman microscopy was demonstrated. The former technique permits the examination of the relative concentration of molecular species (e.g., endogenous and exogenous lipids and proteins) over spatial areas, approximately 1 mm, with a spatial resolution of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 37 publications
0
43
0
1
Order By: Relevance
“…36,37 For their studies, Xiao et al used deuterated phospholipids. Labeling molecules with deuterium permits to facilitate their detection, since CÀ ÀD bonds arise between 2000 and 2250 cm 21 , a spectral domain free of vibrations from biological constituents.…”
Section: Molecular Characterization Of Reconstructed Skin Model 271mentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 For their studies, Xiao et al used deuterated phospholipids. Labeling molecules with deuterium permits to facilitate their detection, since CÀ ÀD bonds arise between 2000 and 2250 cm 21 , a spectral domain free of vibrations from biological constituents.…”
Section: Molecular Characterization Of Reconstructed Skin Model 271mentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] The follow-up, in real-time analysis, of the diffusion of the exogenous products through skin layers has also been performed. [35][36][37] To evaluate the potential of the Raman spectroscopy for future investigations on reconstructed skin samples, such as percutaneous absorption studies, toxicological risks investigations, drugs development, cosmetic products safety, and assessment of the effect of environmental aggressions like UV radiations, we have tried for the first time to establish a vibrational identity and a spectral characterization of a synthetic epidermis model, Episkin 1 , reconstructed from a culture of keratinocytes on a type-I collagen matrix. In a second time, we have realized a comparative study between the spectral signature of Episkin and the signature of human epidermis from excised skin.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro follow-up studies of metronidazole [12] and phospholipids [13] indicated the potential of confocal Raman microscopy for penetration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the experiments was performed in vitro with excised skin samples spanning from the characterization of barrier structures and changes upon cell maturation or diseased state up to permeation of substances and particles into skin [6].…”
Section: Looking At Barriers and Transport Processes With Modern Micrmentioning
confidence: 99%